Risk factors and socioeconomic determinants of falls among older adults - Agnieszka Maruszewska; Tadeusz Ambroży; Łukasz Rydzik (Frontiers in Public Health)
BackgroundFalls are included in this category due to their high prevalence among people over 60 years of age. The aim of this study is to analyze the relationship between the frequency of falls and selected socioeconomic factors.MethodsThe study was conducted among 351 patients of a rehabilitation clinic and center. The research method was a structured diagnostic survey using the Falls Risk Assessment Tool (FRAT) to collect data on fall incidence and associated risk factors.ResultsA significant relationship was found between the age of the participants, their level of education (p = 0.00015), and the type of work previously performed (p = 0.00039) and the frequency of falls. The frequency of falls increased with age, and falls were more common among less educated individuals and those who previously performed physical work. A significant relationship was also found between marital status (p = 0.00039), material status (p = 0.004), and the number of people in the household (p = 0.002) and the frequency of falls. Falls were most frequent among widowed individuals and those with poorer financial situations. People living alone and those living in households with more than two members experienced falls more often.ConclusionsThese findings suggest that educational background and financial constraints may contribute to fall risk, emphasizing the need for targeted fall prevention programs among vulnerable populations.